A CONCISE REVIEW ON CALCIFIED CANALS - A REVIEW - E., Thariny; K, Anjaneyulu; Brundha, M.P (International Journal of Psychosocial Rehabilitation, 2020)
A calcified canal is a root canal system complication due to hard tissue deposition which makes the canal narrower. Calcification is uncontrolled due to enzyme failure that could result in reduced blood supply to the tissue. Canal calcification is usually termed as an obliteration of the pulp canal. Pulp canal obliteration (PCO) or calcific metamorphosis as sequelae of dental trauma may also occur as sequelae of aging, dental caries, tooth loss or critical pulp therapy, orthodontic care. Extreme physiologic PCO in geriatric patients can arise from secondary or tertiary dentine apposition. Despite the application of high-magnification and cone-beam computed tomographic (CBCT) imaging, access cavity preparation for such cases is prone to procedural errors that may result in substantial loss of dentin structure, thus reducing the long-term prognosis. With the aid of advanced technology, early detection of canal obliteration will save a lot of frustrations. Early intervention as a prophylactic measure may not be reasonable, due to the low incidence of such teeth developing periapical pathosis. Hence, it is important to explain prophylactic action, if intended. Upon failure of other treatment modalities surgical intervention may be a possibility. Given the difficulty in its management, it is recommended that teeth showing signs of obliteration be referred to an Endodontist who can handle such cases with minimal errors in conjunction with specialist training, magnification, proper equipment, and detailed knowledge of dental anatomy, thereby providing a better prognosis. This analysis assists in information about the calcified canals about their etiology, possible modes of growth, diagnosis, and management, thereby helping to provide better treatment quality.